2012
DOI: 10.1186/2251-6581-11-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Mobile phone text messaging and Telephone follow-up in type 2 diabetic patients for 3 months: a comparative study

Abstract: BackgroundTo investigate and to compare the effectiveness of a nurse short message service (SMS) by cellular phone and telephone follow-up by nurse on Glycosylated hemoglobin (HbA1c) levels in people with type 2 diabetes.MethodsSemi experimental study consisted of 77 patients with type 2 diabetes that randomly assigned to two groups: telephone follow-up (n = 39) and short message service (n = 38). Telephone interventions were applied by researcher for 3 months. SMS group that received message daily for 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 22 publications
2
43
0
3
Order By: Relevance
“…We have chosen the length of the intervention to be three months for two main reasons. First, previous studies have confirmed that a three-month period is sufficient to detect a significant change in medication adherence [7072]. Second, according to Slovak law [68], chronic patients can receive their medication for a maximum of three months.…”
Section: Methodsmentioning
confidence: 99%
“…We have chosen the length of the intervention to be three months for two main reasons. First, previous studies have confirmed that a three-month period is sufficient to detect a significant change in medication adherence [7072]. Second, according to Slovak law [68], chronic patients can receive their medication for a maximum of three months.…”
Section: Methodsmentioning
confidence: 99%
“…Seis de los ocho estudios incluidos mantuvieron contacto exclusivo a través de mensajes de texto, en uno se utilizó una llamada telefónica semanal 17 del proveedor de cuidados al paciente si no tenía información de éste después de tres días de la fecha señalada para comunicar resultados, mientras que en otro estudio además se comparó el uso los SMS con las llamadas a teléfono fijo 23 (Tabla 3).…”
Section: Tabla 2 Resultados De La Intervención Sobre Los Niveles De unclassified
“…En dos de los estudios se utilizó apoyo mediante llamada telefónica 17,23 , uno utilizó video de cuidados 18 y los cinco restantes mencionaron el envío de mensajes de contenido educativo y motivacional; por lo anterior se infiere que no se contó con uniformidad entre las intervenciones que puedan demostrar que exclusivamente el envío de SMS es una estrategia efectiva para el control glucémico de los pacientes con DT2 al mantener o reducir las cifras de hemoglobina glucosilada iguales o menores a niveles de 7%.…”
Section: Enfermería Globalunclassified
See 1 more Smart Citation
“…Through the use of technology, we can get beyond traditional referral letters to real-time consultation and exchanges with patients and providers in different locations. Primary care providers, specialists, care teams, and individual patients can benefit from problem or case-based learning, collaborating across geographical boundaries through the use of chat, voice, and video communications (Basoglu et al, 2012; Istepanian et al, 2009; Lyles et al, 2011; Rabin & Bock, 2011; Zolfaghari et al, 2009). These technologies will allow providers to jointly inform patients about guidelines and information pertinent to their care without lengthy waits between primary care visits and specialist appointments.…”
Section: Methodsmentioning
confidence: 99%